The Hebrew prophets : an introduction - Lundbom, Jack R. (Minneapolis, MN : Fortress Press, 2010)
Noting that the legacy of the prophets remains a powerful element in contemporary society, Jack R. Lundbom explores the contours of prophetic speech in ancient Israel. He surveys the elements of each prophets message, describes the characteristics of prophetic rhetoric and symbolic behavior, and discusses the problem of authenticity: how did individuals make the claim to speak as prophets, and how did their audiences recognize their claims? The Hebrew Prophets offers an authoritative introduction to the phenomenon of ancient prophetic speech for the contemporary reader--and hearer.
Pt. 1. Marks, messages, and measures of authenticity in the Hebrew prophets. To be a prophet... -- The prophetic message : what is it? -- Measures of authenticity -- Pt. 2. Poetry, prose, rhetoric, and symbolism in the Hebrew prophets. Prophetic discourse in poetry and prose -- Rhetorical discourse in the prophets -- Prophetic signs, wonders, and symbolic behavior.
Includes bibliographical references (p. 231-235) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc